2021
DOI: 10.3390/ijerph182111599
|View full text |Cite
|
Sign up to set email alerts
|

The Cost Effectiveness of Ecotherapy as a Healthcare Intervention, Separating the Wood from the Trees

Abstract: Internationally, shifts to more urbanised populations, and resultant reductions in engagements with nature, have been a contributing factor to the mental health crisis facing many developed and developing countries. While the COVID-19 pandemic reinforced recent trends in many countries to give access to green spaces more weight in political decision making, nature-based activities as a form of intervention for those with mental health problems constitute a very small part of patient pathways of care. Nature-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The body of evidence regarding the physical and mental benefits of NBIs is steadily expanding, but research on their cost-effectiveness is limited. A recent scoping review found that there is potential for NBIs to be cost-effective for people with mild-to-moderate com-mon mental health problems, but more research is needed, such as a randomized controlled trial with sufficient statistical power and follow-up, to confirm these findings [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The body of evidence regarding the physical and mental benefits of NBIs is steadily expanding, but research on their cost-effectiveness is limited. A recent scoping review found that there is potential for NBIs to be cost-effective for people with mild-to-moderate com-mon mental health problems, but more research is needed, such as a randomized controlled trial with sufficient statistical power and follow-up, to confirm these findings [22].…”
Section: Discussionmentioning
confidence: 99%
“…While the existing evidence on the cost-effectiveness of NBIs for treating mental health challenges is currently insufficient for the National Institute of Health and Care Excellence (NICE) to conduct a meaningful assessment and provide clinical guidance, SROI analysis is increasingly being used to estimate the wider benefits of NBIs [22].…”
Section: Discussionmentioning
confidence: 99%
“…Such a gap in public knowledge creates an opportunity for yoga studios and companies manufacturing and promoting yoga apparel to create “empowerment” marketing and digital ads that offer relevant and evidence-based information ( Figure 1B ). Since nature therapies such as eco-therapy and forest bathing gain more recognition for their clinical effects ( 92 , 93 ), advertising health benefits of connection with nature can be a part of health promotion campaigns ( 94 ). It is noteworthy that “positive-gain” message framing has been shown to be more effective in promoting health-related behaviors ( 95 , 96 ).…”
Section: Digital Marketing Of Consumer Products and Services Promotin...mentioning
confidence: 99%
“…Currently, the evidence base is not clear about the optimum duration of exposure for maximum health gain or whether individuals with particular mental disorders may respond better. Furthermore, while evidence suggests that green social prescriptions are likely to be cost-effective for individuals with mild to moderate mental illness [46]; further research is required to demonstrate the magnitude of these benefits and the potential social and wider returns on investment. It is also reported that while mental health clinicians perceive nature-based interventions to provide a range of health benefits for individuals with mental illness including improved mood, wellbeing, and social connections; there are concerns over barriers to use of services, such as individuals’ mental health symptoms, lack of motivation and geographical accessibility [47,48].…”
Section: Green Social Prescribing For Mental Health and Mental Illnessmentioning
confidence: 99%